2018
DOI: 10.1007/s10895-018-2212-9
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal Form of Tetra(Aryl)Tetracyanoporphyrazine: Physical Properties and Photodynamic Activity In Vitro

Abstract: Tetra(aryl)tetracyanoporphyrazines are the promising group of dyes for photodynamic therapy of tumors with unique combination of photosensitizer properties and sensitivity of fluorescence parameters to the environment viscosity. However, in vivo application of such hydrophobic photosensitizers requires using of drug carriers ensuring efficient delivery to the tumor site. The present study is focused on obtaining liposomes loaded with tetrakis(4-benzyloxyphenyl)tetracyanoporphyrazine and examining their propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Notably, in the dark, no toxicity of this compound was observed ( Figure 1 , black curve ). Earlier [ 27 ], it was shown that for A-431 human epidermoid carcinoma cells, the IC 50 value of porphyrazine under similar irradiation conditions was significantly lower: 0.68 μM. The difference may be due to a relatively high resistance of SKOV-3 cells to this photosensitizer.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Notably, in the dark, no toxicity of this compound was observed ( Figure 1 , black curve ). Earlier [ 27 ], it was shown that for A-431 human epidermoid carcinoma cells, the IC 50 value of porphyrazine under similar irradiation conditions was significantly lower: 0.68 μM. The difference may be due to a relatively high resistance of SKOV-3 cells to this photosensitizer.…”
Section: Resultsmentioning
confidence: 90%
“…One of the proposed approaches to solving the problem is to use vehicles capable to increase the tissue penetration of photodynamic agents. Liposomes, organic and hybrid nanoparticles, membrane-based vesicles have been tried for this role [ 27 , 32 , 35 , 37 ]. The advantages of such carriers are expected to increase the efficacy of photodynamic therapy.…”
Section: Resultsmentioning
confidence: 99%
“…A comprehensive review on liposomal antitumor formulations is provided elsewhere [55,56]. The further directions in antitumor liposomal formulations progress are the development and improvement of stimuli-sensitive smart liposomes (thermo-, redox-, ultrasound-, enzyme-sensitive), magnetic liposomes, and liposomes for photodynamic therapy [57,58,59,60,61,62,63].…”
Section: Passive Targetingmentioning
confidence: 99%
“…Notably, the developed nanocarriers had less dark toxicity than the photosensitizer itself. Another example is the loading of tetracyanotetra(aryl)porphyrazines into liposomes [ 42 ]. Thus, in addition to their low toxicity, pz II and pz IV can be encapsulated in a nano-sized vehicle for improvement of the targeted delivery to the tumor tissue via an enhanced permeability and retention effect.…”
Section: Discussionmentioning
confidence: 99%